A Framework for Analyzing Malpractice Cases to Improve Healthcare Systems. (10th August 2015) - Dror, Shuki; Margol, Dina; Ograjenšek, Irena; dos Reis, Marco Seabra
<x xml:space="preserve">Abstract</x> This study develops a framework for analyzing the judgments handed down by courts in malpractice cases. We analyzed 215 cases that included awards for damages caused by medical negligence, handled by Israeli courts from 2005 to 2011. The Pareto principle coupled with the mean square error criterion supports the selection of the vital hospital departments and the vital causes of claims. A quality function deployment matrix is used to translate the desired improvement in malpractice costs into relevant medical decisions and diagnostic tests. Based on the analysis, we can conclude that the essential part of all malpractice claims submitted to and found legitimate by the courts was related to the obstetrics field. We reveal that most claims have elements in common. When we based the analysis on the malpractice compensation, covering costs of corrective treatment, suffering, future medical treatment, and associated legal fees, based on court data, we found that the group of vital causes decreased. In this study, we analyze claims related to the obstetrics department. Other departments where errors are frequently made should be addressed in turn, with the objective of continuously improving the medical system. Copyright © 2015 John Wiley & Sons, Ltd.